1998
DOI: 10.3109/08923979809034816
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Quercetin, Immune Functions and Colonic Carcinogenesis in Rats

Abstract: Rats fed 100 mg/kg quercetin (QUE) daily for 7 weeks had significantly enhanced natural killer cell activity compared to their vehicle (VEH)-fed control. In contrast, rats fed 100 mg/kg QUE and treated with the colon carcinogen, azoxymethane had significantly reduced natural killer cell activity compared to their VEH-fed azoxymethane-treated control. There was no significant difference in natural killer cell activity between the two control groups. Antibody production and delayed-type hypersensitivity were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
2
15
2
Order By: Relevance
“…A metaanalysis of 4 polyp-recurrence human intervention trials and 4 carcinogen-treated animal studies indicated that there was no protective effect of β-carotene supplementation [4] against colon tumor formation. Quercetin supplementation studies also showed inconsistent results in carcinogen-treated colon cancer models [1,5,13,17]. These results and the results from the present study suggest that it may be too early to conclude dietary quercetin and β-carotene are effective in colon cancer prevention, and more in vivo intervention studies are required.…”
Section: Discussioncontrasting
confidence: 59%
“…A metaanalysis of 4 polyp-recurrence human intervention trials and 4 carcinogen-treated animal studies indicated that there was no protective effect of β-carotene supplementation [4] against colon tumor formation. Quercetin supplementation studies also showed inconsistent results in carcinogen-treated colon cancer models [1,5,13,17]. These results and the results from the present study suggest that it may be too early to conclude dietary quercetin and β-carotene are effective in colon cancer prevention, and more in vivo intervention studies are required.…”
Section: Discussioncontrasting
confidence: 59%
“…Several studies have investigated the effect of wine flavonoids on NK cell function. While quercetin in vitro (1 mM) significantly decreased lytic activity of NK cells (no effects at lower concentrations) (Exon et al, 1998), in animal models, quercetin (100 mg/kg) and catechin (125-500 mg/kg) increased lytic activity of NK cells (Ikeda et al, 1984;Exon et al, 1998). The doses used in in vitro studies and those obtained in the animal studies were much higher than the plasma flavonoid concentrations in our study subjects after a single intake of these beverages.…”
Section: Discussionmentioning
confidence: 49%
“…No specific biological pathways were modulated in the ileum and only a single, yet highly relevant, pathway was identified in the colon (antigen presentation). Interestingly, the great majority of studies examining quercetin in the intestine have focused on its role on cell proliferation, apoptosis, and carcinogenesis, while little work has focused on its role in immune function (11). This fact may stem from the use of common carcinomic cell culture models (e.g., Caco-2, HT-29, T84 cells, etc.)…”
Section: Discussionmentioning
confidence: 99%